THE INFLUENCE OF LIFESTYLE, FINANCIAL LITERACY ON THE CONSUMPTIVE BEHAVIOR OF THE MILLENNIAL GENERATION IN THE COVID-19 PANDEMIC ERA IN PADANG - Dul Candra; Bintang Aulia Lutfi (Universitas Airlangga, 2022)
Purpose: This research to determine the effect of lifestyle, literacy on the consumptive behavior of the millennial generation in the Covid-19 pandemic era in Padang. Methods: The method used in this research uses quantitative analysis with the sample method of respondents using the stratified random sampling method, the research subject is the Millennial generation. Results: In this research, we get the results that many generations today are living a lifestyle that can be called hedonism because they cannot manage their finances and result in consumptive behavior in their lives. We estimate that this is due to the very fast development of the times that the millennial generation must follow. Conclusion and Suggestion: The results of the study reveal that lifestyle and financial literacy have a positive effect on the consumptive behavior of the millennial generation at this time which results in falling into the development of an increasingly modern era. It is hoped that the millennial generation must be able to cope with the times by avoiding relationships or a hedonistic lifestyle, and being able to manage financial management both in normal times and in times of economic difficulty during the Covid-19 pandemic, and it is hoped that the millennial generation is more concerned with needs than desires in consuming an item.